The Escarpão Plateau (South of Portugal) - A study case of nesting geosites from the aspiring algarvensis geopark - Veiga-Pires, Cristina (2022)
Located along the southern limit of the aspiring algarvensis UGGp, the Escarpão Plateau is a singular geomorphological structure sculpted by the conjugation of fluvial, karst and tectonic processes. The plateau is deeply scarved by the Quarteira Rivulet forming a valley that crosses the most complete sedimentary sequence of the Upper Jurassic of the Eastern Algarve (161,2 to 145,5 million years).